Treatment outcomes of TB‐infected individuals attending public sector primary care clinics in rural Liberia from 2015 to 2017: a retrospective cohort study. Issue 5 (16th April 2018) - Wickett, Eugene; Peralta‐Santos, André; Beste, Jason; Micikas, Mary; Toe, Foriest; Rogers, Julia; Jabateh, Lassana; Wagenaar, Bradley H.
Abstract: Objectives: In June 2015, Partners in Health (PIH) and the Liberian Ministry of Health began a community health worker (CHW) programme containing food support, reimbursement of transport and social assistance to address gaps in tuberculosis (TB) treatment exacerbated by the 2014‐2015 Ebola virus disease (EVD) epidemic. The purpose of this article was to analyse the performance of routine clinical TB care and the effects of this CHW programme. Methods: Retrospective cohort study utilising data from TB patient registers at a census of all health facilities treating TB in the south‐east region of Liberia from January 2015 – April 2017. Competing risks Cox regression analyses were used to generate subhazard ratios (sHR) analysing factors associated with rates of TB cure (smear negative), treatment completion (no smear), lost to follow‐up (LTFU) and death. Results: LTFU rates decreased 76% pre‐ vs . post‐CHW intervention, from 14.6% in pre‐intervention to 3.4% post‐intervention ( P < 0.001). Although the post‐intervention had better cure rates (sHR 1.07, CI 0.58‐1.9), treatment completion (sHR 1.53, CI 1.00 2.39) and lower death rates (sHR 0.64, CI 0.34‐1.2), statistical significance was not reached. Younger patients had significantly lower death and cure rates, while older patients had higher LTFU and cure rates. Overall, 31% of patients were cured, 44% completed treatment without a confirmatory smear, 5% were LTFU, 9% died, 0.5% failed treatment, and 10% transferred out. Conclusions: In challenging environments, LTFU can be reduced by CHW accompaniment and socio‐economic assistance to patients with TB. Approaches are needed to improve cure verification in young patients and reduce mortality.